Canada Goose Management Series: Nest and Egg Destruction - Drake, David (Rutgers New Jersey Agricultural Experiment Station, Rutgers Cooperative Extension, 2004)
There is a wide range of non-lethal and lethal options available for Canada goose ( Branta canadensis ) management. This fact sheet, part of a series that examines goose management options currently employed, will present information on nest and egg destruction techniques that may be used to remove geese from your property. We define the techniques and explore the advantages and disadvantages of nest and egg destruction in terms of, among other factors, amount of effort required to implement, effectiveness, and cost. Fact Sheet FS1030 Purpose: To provide information about managing Canadian geese by nest and egg destruction